PASSOMPE’S TRADITION: Tracing Back the Maritime Culture of South Sulawesi’s People in Southeast Asia before the 16th Century - Ridhwan Ridhwan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This article examines the traces of South Sulawesi's maritime culture in Southeast Asia and before the sixteenth century. The choice of a period prior to the 16th century is based on the fact that existing literature on the subject generally mentions the involvement of South Sulawesi merchant seamen in trade in Southeast Asia and even Asia, which occurred in the first half of the 20th century AD 16 century or earliest second half of the 15th century. These writings always refer to the 1512 voyages of the Portuguese navigator Tom Pires, who found merchants from the island of Macassar establishing trade with various parts of Southeast Asia. However, based on the authors' assessment of available external and local sources, it is concluded that their involvement dates back to the first century AD.